The Concept of Manhaj Tarjih and Tajdid in a Muhammadiyah Perspective - Imro Atus Soliha; Romelah; Nurul Humaidi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Social development becomes an inevitable reality in the dynamics of social life. The social transformation that occurs in society certainly influences Islamic law as a system of social norms that are directly related to human behavior. This article aims to conduct a literature-based analysis, exploring manhaj tarjih and tajdid in the Muhammadiyah tradition as a basis for developing thinking. Islamic studies at Muhammadiyah are not only limited to the framework of religious studies, but also as a process of understanding Islam as a whole, with the aim of bringing Islam as a blessing for all of nature (rahmatan lil alamin). This approach is not limited to the conceptual realm, but rather focuses on real applications, in accordance with the philosophical principles of baldatun toyyibatun wa rabbun ghofur. Using a historical analysis approach, the author assesses that Muhammadiyah's ijtihad method in responding to social change is dynamic and progressive, adopting and developing three approaches, namely bayani, tahlili, and istislahi.